Development of an intelligent air-cushion system for a swamp tracked vehicle - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Aminanda, Yulfian; Muhidin, Arifin (2010)
This paper describes the unique structure of an intelligent air –cushion system for an intelligent air-cushion track vehicle (IACTV) working on swamp terrain and its performance. Based on the total motion resistance and driving force analyzing for IACTV, the load distribution for the intelligent air-cushion system and propulsion system are investigated respectively for minimizing the total power consumption. Two main issues are studied in this paper. First, a theoretical model is developed for optimizing total power consumption of the vehicle and the effects of load distribution on vehicle tractive effort and motion resistance. Secondly, the vehicle has the ability to response for the changeable cushion pressure based on the clearance height. The system is effective to control the intelligent air –cushion system with measuring the vehicle tractive effort (TE), motion resistance (MR), power consumption (PC), cushion clearance height (CH) and cushion pressure (CP). Ultrasonic displacement sensor, pull-in solenoid electromagnetic switch, pressure control sensor, micro controller, and battery pH sensor are incorporated with the Fuzzy logic controller to investigate experimentally the TE, MR, PC, CH, and CP. Experiment and simulation results showed that the optimal power consumption can be obtained and maintained by using the designed control system with the load distribution ratio as 0.2.